2019
DOI: 10.1007/s12192-019-00976-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high-fat, high-sugar diet and bariatric surgery on HSP70 and HSP90 plasma and liver concentrations in diet-induced obese rats

Abstract: Metabolic surgery ameliorates insulin resistance and is associated with long-term, effective weight loss, but the mechanisms involved remain unknown. Here, the duodenal-jejunal omega switch (DJOS) surgery in combination with high-fat, high-carbohydrate diet was performed on diet obese rats and joint effects of bariatric surgery and different dietary patterns on heat shock protein 70 (HSP70) and HSP90 plasma and liver concentrations were measured. We found that plasma and liver levels of HSP70 were lower after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…Garamyolgyi et al showed that HSPA4 levels correlated well with HbA1c in gestational diabetes [53]. Our work demonstrates a significant reduction in HSPA4 which correlated with percentage change in IL6 between baseline and 12 months (r = 0.87, p < 0.001), this is in keeping with previous work by Styger et al who demonstrated reduction in both serum and liver HSPA4 in a murine model after BS [54] and also is in agreement with the narrative that HSPA4 appears to be induced by states of chronic inflammation [55]. Some have suggested targeting these proteins as therapy for T2DM [56].…”
Section: Discussionsupporting
confidence: 92%
“…Garamyolgyi et al showed that HSPA4 levels correlated well with HbA1c in gestational diabetes [53]. Our work demonstrates a significant reduction in HSPA4 which correlated with percentage change in IL6 between baseline and 12 months (r = 0.87, p < 0.001), this is in keeping with previous work by Styger et al who demonstrated reduction in both serum and liver HSPA4 in a murine model after BS [54] and also is in agreement with the narrative that HSPA4 appears to be induced by states of chronic inflammation [55]. Some have suggested targeting these proteins as therapy for T2DM [56].…”
Section: Discussionsupporting
confidence: 92%
“…That may suggest that changes in the dietary protocol before and after DJOS surgery change the physiological and biochemical pathways and lead to metabolic influence PTX3 levels compared to SHAM-operated rats. Together with insignificant bodyweight reduction in the DJOS-operated rats, described in the previous study [ 36 ], we postulate that bariatric protocol does not reduce deleterious effects of the HFS/HFS diet. The postulate can be supported by no significant changes in PTX3 concentration observed in DJOS-operated rats.…”
Section: Discussionsupporting
confidence: 59%
“…Studies on bariatric surgery effects showed that gastric banding could increase plasma PTX3 concentrations in morbidly obese patients six months or one year after weight reduction [ 35 ]. The results of two separate experiments, where we used HF [ 22 ] or HFS [ 36 ] diets, showed that a diet change after DJOS surgery to a more caloric one, regardless if it was HF or HFS, did not lead to significant weight loss [ 22 , 36 ]. In our previous separate study on this animal model, we observed that a high fat diet reduced the effects of the surgery compared to groups of rats fed with the control diet [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSPA4 has also been associated with inhibition of nitric oxide production correlating with CRP levels in individuals with T2DM [19]. Styger et al demonstrated reduction in both serum and liver HSPA4 in a murine model after MBS [24]. Our work demonstrates a significant reduction in HSPA4, which correlated with percentage change in IL6 between baseline and 6 months; however, this correlation was not maintained at 12 months.…”
Section: Discussionsupporting
confidence: 41%